Menerapkan prinsip service excellent dalam pelayanan gereja berdasarkan Kolose 3:23 - Ardiyanto, Yudha; Sartika, Meitha; Meriyana, Meriyana (Davar : Jurnal Teologi, 2024)
ABSTRACT This study discusses the application of the principle of service excellent in church services based on Colossians 3:23, with a qualitative descriptive approach through a literature review. Service excellent, which is commonly used in the business world, is adapted in the church context to improve the quality of service and congregational engagement. Colossians 3:23 is the theological foundation that encourages church servants to serve with all their hearts, as if for God, not for humans. Through literature analysis, including theological books, trusted scientific journals, and the Bible. This study identifies ways in which churches can implement the principles of excellent service, such as reliability, empathy, and attention to the needs of the congregation. The results of the study indicate that the application of service excellent contributes to increased satisfaction and congregational engagement and strengthens the church community. This study is expected to provide practical guidance for today's churches to implement quality services that are in line with Christian values. Keywords: Service Excellent, Service, Church, Theological, Practical.  ABSTRAKPenelitian ini membahas penerapan prinsip service excellent dalam pelayanan gereja berdasarkan Kolose 3:23, dengan pendekatan deskriptif kualitatif melalui kajian pustaka. Service excellent, yang umumnya digunakan dalam dunia bisnis, disesuaikan dalam konteks gerejawi untuk meningkatkan kualitas pelayanan dan keterlibatan jemaat. Kolose 3:23 menjadi landasan teologis yang mendorong pelayan gereja untuk melayani dengan segenap hati, seolah-olah untuk Tuhan, bukan untuk manusia. Melalui analisis literatur, termasuk buku-buku teologi, jurnal ilmiah terpercaya, dan Alkitab. Penelitian ini mengidentifikasi cara-cara gereja dapat mengimplementasikan prinsip-prinsip service excellent, seperti keandalan, empati, dan perhatian pada kebutuhan jemaat. Hasil penelitian menunjukkan bahwa penerapan service excellent berkontribusi pada peningkatan kepuasan dan keterlibatan jemaat serta memperkuat komunitas gereja. Penelitian ini diharapkan memberikan panduan praktis bagi gereja masa kini untuk menerapkan pelayanan berkualitas yang selaras dengan nilai-nilai Kristen. Kata kunci: Service Excellent, Pelayanan, Gereja, Teologis, Praktis.